Angular cheilitis and oral pigmentation as early detection of Peutz-Jeghers syndrome - Maharani Laillyza Apriasari; Amy Nindia Carabelly (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2018)
Background: Peutz-Jeghers syndrome (PJS) is an inherited autosomal dominant disease determined by a mutation localized at 19p13.3 characterized by the occurrence of gastrointestinal hamartomatous polyps in association with mucocutaneous hyperpigmentation. The manifestation of PJS may first be encountered by a dentist during routine examination due to the presence of pigmented spots in the oral cavity. Purpose: To prevent a high risk of PJS, the dentist must establish its oral manifestation through early detection. Case: A 14-year-old male patient attended complaining of a week-long pain at the corners of the lips. An extra-oral exam revealed fissure lesions, redness, white crust and pain. The patient had experienced bleeding in his bowel movements, abdominal pain, nausea and vomiting since childhood. A number of black, painless, macular lesions, some 1-3 mm in diameter, were present on the upper lips, lower lips, fingers and palms. Case management: The patient was referred for a complete blood count check. The results obtained confirmed him to be suffering from severe anemia and he was, therefore, referred to an internist for treatment for PJS. Conclusion: It can be concluded that the early detection of PJS is crucial in order that the patient receives prompt treatment.